Analysis of Factors Influencing Fraudulent Financial Statements: Pentagon Fraud Perspective and Managerial Ownership - Putra Wahyu Manuhara; Utami Budi Barata Kusuma; Islami Dian (SHS Web of Conferences)
Financial statement fraud poses a significant threat to the integrity of financial reporting and investor confidence so will become a threat to sustainability and business continuity. This study aims to analyze the factors that influence fraudulent financial statements from the perspective of the Pentagon fraud theory and managerial ownership. The fraud pentagon model consists of financial target, financial instability, independent commissioners, receivable related party transactions, debt related party transactions, change of auditor, change of directors, number of CEO photos and adding other variable managerial ownership. The population of this research is 108 companies on the IDX for the 2011-2020 period using a purposive sampling method. The sample consists of 54 fraud companies and 54 non-fraud companies. The research results prove that receivables related party transactions and changing auditors have positive effect on financial statement fraud. Meanwhile, the variables of financial target, financial instability, independent commissioner, debt related party transactions, change of directors, number of CEO photos and managerial ownership have no effect on financial report fraud.